2018
DOI: 10.1186/s12944-018-0802-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating full-length angiopoietin-like protein 8 and non-high-density lipoprotein cholesterol levels in Chinese non-diabetic individuals: a cross-sectional study

Abstract: BackgroundAngiopoietin-like protein 8 (ANGPTL8) is a novel hormone involved in the regulation of lipid metabolism and glucose homeostasis. There are inconsistent results regarding the association between ANGPTL8 and lipids in humans. We aimed to investigate the associations between ANGPTL8 and lipids in people without diabetes.MethodsThis was a cross-sectional study of 107 patients with dyslipidemia and 141 patients without. Dyslipidemia diagnosis was based on Chinese guidelines for the prevention and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…ANGPTL8 was also related to TG and CHOL in patients with hyperlipidemia after adjusting age, sex, BMI, alanine aminotransferase, hypersensitive C-reactive protein and CREA. In agreement to our findings on PNS patients, serum ANGPTL8 level was found to be positively associated with CHOL, but not with HDL-C and LDL-C [14].…”
Section: Hyperlipidemia Symptom Occurs In Pns Patients Involving Two supporting
confidence: 92%
See 1 more Smart Citation
“…ANGPTL8 was also related to TG and CHOL in patients with hyperlipidemia after adjusting age, sex, BMI, alanine aminotransferase, hypersensitive C-reactive protein and CREA. In agreement to our findings on PNS patients, serum ANGPTL8 level was found to be positively associated with CHOL, but not with HDL-C and LDL-C [14].…”
Section: Hyperlipidemia Symptom Occurs In Pns Patients Involving Two supporting
confidence: 92%
“…Previous studies report ANGPTL8 detected both in human serum and mouse serum [9], as well as in human urine samplemoderates [10]. It's also recently observed that the serum levels of ANGPTL8 is significantly increased in patients with metabolic diseases such as type 2 diabetes [10,11], hyperlipidemia [12][13][14], non-alcoholic fatty liver [15] and so on. Moreover, in type 2 diabetes patients, the elevated serum ANGPTL8 level are associated with their increased risk of diabetic nephropathy, suggesting ANGPTL8's possible role in kidney damage [10].…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies revealed an association between ANGPTL3 and ANGPTL8 with lipid biomarkers in adults, young obese non-diabetic men, children, and adolescents with obesity and metabolic syndrome. However, very few of them stratified their data by gender [5,6,[14][15][16]. We selected circulating ANGPTL3 and ANGPTL8 to assess gender-specific relationships with obesity and biomarkers of atherogenic lipid profile in non-diabetic adults aged between 25 and 74 years.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05 were adjusted in logistic regression in this study. ANGPTL8 was also reported to be negatively associated with HDL-C levels [42], while multiple logistic regression analysis showed that ANGPTL8 was associated with TAD after adjusting for HDL-C. Numerous studies have demonstrated that ANGPTL8 levels are positively correlated with FPG and insulin resistance [43].…”
Section: Discussionmentioning
confidence: 99%